Expression of SIRT1 and DBC1 is associated with poor prognosis of soft tissue sarcomas. - Jung Ryul Kim; Young Jae Moon; Keun Sang Kwon; Jun Sang Bae; Sajeev Wagle; Taek Kyun Yu; Kyoung Min Kim; Ho Sung Park; Ju-Hyung Lee; Woo Sung Moon; Ho Lee; Myoung Ja Chung; et al. (PLoS ONE, 2013)
Recently, the roles of SIRT1 and deleted in breast cancer 1 (DBC1) in human cancer have been extensively studied and it has been demonstrated that they are involved in many human carcinomas. However, their clinical significance for soft-tissue sarcomas has not been examined. In this study, we evaluated the expression and prognostic significance of the expression of SIRT1, DBC1, P53, β-catenin, cyclin D1, and KI67 in 104 cases of soft-tissue sarcomas.Immunohistochemical expression of SIRT1, DBC1, P53, β-catenin, and cyclin D1 were seen in 71%, 74%, 53%, 48%, and 73% of sarcomas, respectively. The expression of SIRT1, DBC1, P53, β-catenin, and cyclin D1 were significantly correlated with advanced clinicopathological parameters such as higher clinical stage, higher histological grade, increased mitotic counts, and distant metastasis. The expression of SIRT1, DBC1, P53, β-catenin, cyclin D1, and KI67 were significantly correlated with each other and positive expression of all of these predicted shorter overall survival and event-free survival by univariate analysis. Multivariate analysis revealed the expression of SIRT1 as an independent prognostic indicator for overall survival and event-free survival of sarcoma patients. In conclusion, this study demonstrates that SIRT1- and DBC1-related pathways may be involved in the progression of soft-tissue sarcomas and can be used as clinically significant prognostic indicators for sarcoma patients. Moreover, the SIRT1- and DBC1-related pathways could be new therapeutic targets for the treatment of sarcomas.